Ozone, heat and mortality: acute effects in 15 British conurbations. Issue 10 (25th August 2010) - Pattenden, Sam; Armstrong, Ben; Milojevic, Ai; Heal, Mathew R; Chalabi, Zaid; Doherty, Ruth; Barratt, Ben; Kovats, R Sari; Wilkinson, Paul
Abstract : Background: Acute associations between mortality and ozone are largely accepted, though recent evidence is less conclusive. Evidence on ozone–heat interaction is sparse. We assess effects of ozone, heat, and their interaction, on mortality in Britain. Methods: Acute effects of summer ozone on mortality were estimated using data from 15 conurbations in England and Wales (May–September, 1993–2003). 2-day means of daily maximum 8-h ozone were entered into case series analyses, controlling for particulate matter with aerodynamic diameter of <10 μm, natural cubic splines of temperature, and other factors. Heat effects were estimated, comparing adjusted mortality rates at 97.5th and 75th percentiles of 2-day mean temperature. A separate model employed interaction terms to assess whether ozone effects increased on 'hot days' (where 2-day mean temperature exceeded the whole-year 95th percentile). Other heat metrics, and non-linear ozone effects, were also examined. Results: Adverse ozone and heat effects occurred in nearly all conurbations. The mean mortality rate ratio for heat effect across conurbations was 1.071 (1.050–1.093). The mean ozone rate ratio was 1.003 per 10 μg/m 3 ozone increase (95% CI 1.001 to 1.005). On 'hot days' the mean ozone effect reached 1.006 (1.002–1.009) per 10 μg/m 3, though ozone–heat interaction was significant in London only. On substituting maximum for mean temperature, the overall ozone effect reduced to null, though evidence remained of effects on hot days, particularly in London. An estimated ozone effect threshold was below current guidelines in 'mean temperature' models. Conclusion: While heat showed robust effects on summer mortality, estimates for ozone depended upon the modelling of temperature. However, there was some evidence that ozone effects were worse on hot days, whichever temperature measure was used.